Glycyrrhizic acid assists anti-psoriatic efficacy of a self-deformable curcumin loaded transdermal gel. (16th March 2022) - Jin, Nan; He, Jingwen; Wu, Chenyuan; Chen, Zejun; Li, Yuling; Chen, Jianmin; Lin, Jianhu
Abstract: The aim of this study was to explore the function of glycyrrhizic acid (GA) in an anti-psoriatic dermal delivery, whereby GA is originally designed as the matrix agent, with curcumin (Cur) as the active agent and silica as the drug carrier. Formulations with different GA proportions were prepared and named W-GA (without GA), L-GA (13% w/w GA) and H-GA (26% w/w GA). The results showed that GA had no significant effect on the physical characteristics, such as particle size and amorphous state, as exhibited by scanning electron microscopy and x-ray diffractograms, respectively. Compared with W-GA and L-GA, H-GA resulted in 10% less photodegradation of Cur after storage for one month, 0.45 μg more penetrated Cur in the epidermis, 2-fold higher viscosity, fewer signals of imiquimod-induced psoriasiform skin lesions and less histological morphological changes. The findings showed that H-GA significantly inhibited expression of interleukin 17 A in the dermis, and interleukin IL-23 in the epidermis, compared with Cur raw drug powder (RDP), whereas L-GA had no significant effect on the expression. These results indicated that a high GA proportion results in superior anti-psoriatic efficacy. Therefore, Cur-loaded silicas with approximately 26% GA are recommended as the superior formulation for the treatment of psoriasis.